Sex Differences in Estradiol Secretion by Trigeminal Brainstem Neurons - Bereiter, David A.; Thompson, Randall; Rahman, Mostafeezur (Frontiers in Integrative Neuroscience, 2019)
Estrogen status is a significant risk factor in the development of temporomandibular joint disorders (TMD). Classically, estrogen status is thought to derive mainly from ovarian sources; however, it is well known that estradiol (E2) also is synthesized by neurons in the brain. This study tested the hypothesis that E2 is produced by neurons in trigeminal subnucleus caudalis (Vc), the principal site of termination for sensory afferents that supply the temporomandibular joint (TMJ), to modify evoked responses in a model of TMJ nociception in male and female rats. Intra-TMJ injection of the small fiber excitant, allyl isothiocyanate (AIC), increased the levels of E2 collected from microdialysis probes sites at Vc of ovariectomized (OvX) female rats, ipsilateral to the stimulus, whereas males displayed no change. Dialysate levels of E2 collected from probe sites in the Vc contralateral or cerebellum in OvX rats were not affected by TMJ stimulation. Reverse dialysis of anastrozole, an aromatase (ARO) inhibitor, via the probe reduced perfusate levels of E2 in Vc. Systemic administration of letrozole, a non-steroid ARO inhibitor, for 4 days prevented TMJ-evoked increases in masticatory muscle electromyographic (MMemg) activity. ARO-positive neurons were distributed mainly in superficial laminae (I-III) at Vc and cell counts revealed no significant difference between OvX and male rats. Intra-TMJ injection of AIC revealed similar numbers of ARO/Fos dual-labeled neurons in OvX and male rats. By contrast, the percentage of ARO neurons co-labeled for glutamic acid decarboxylase (GAD), the biosynthetic enzyme for GABA, was greater in OvX (35%) than male rats (14%). Few ARO-positive neurons were co-labeled for estrogen receptor alpha. These data indicate that E2 is secreted continuously by Vc neurons and that acute stimulation of TMJ nociceptors evokes further secretion in a sex-dependent manner. Reduced TMJ-evoked MMemg activity after ARO inhibition suggests that locally produced E2 by Vc neurons acts via paracrine mechanisms to modify TMJ nociception in female rats.